The Dietary Inclusion of Ensiled Olive Cake Increases Unsaturated Lipids in Milk and Alters the Expression of Lipogenic Genes in Mammary and Adipose Tissue in Goats - Neofytou, Marina C.; Hager-Theodorides, Ariadne Loukia; Sfakianaki, Eleni; Simitzis, Panagiotis E; Symeou, Simoni; Sparaggis, Dionysis; Tzamaloukas, Ouranios; Miltiadou, Despoina (My University, 2023)
This study aimed to evaluate the effect of the dietary inclusion of ensiled OC on milk yield, composition, fatty acid (FA) profile, and the expression of selected genes involved in lipid metabolism in the udder and adipose tissue of goats. Seventy-two Damascus dairy goats in mid-lactation were assigned randomly to three iso-nitrogenous and iso-energetic diets containing 0, 10, and 20% of ensiled OC as a replacement of forage (OC0, OC10, and OC20, respectively) for 42 days. During weeks 5 and 6 of the trial, dry matter intake, milk yield, milk composition, and FA profiles were recorded, while mammary and perirenal adipose tissue samples were also collected from six animals per treatment from the OC0 and OC20 groups for gene expression analysis. No significant differences were observed among groups concerning milk yield, 4% fat-corrected milk, fat, or protein yield (kg/d). In contrast, the milk fat percentage was gradually increased with increasing OC inclusion rates in the diets, while milk protein percentages were elevated in both OC groups but significantly only in the milk of the OC20 group. The content of FA between C4:0 to C16:0 was reduced, while mono-unsaturated FA (MUFA) concentration was enhanced in the goat milk of OC groups. The OC feeding treatment was associated with the increased mammary expression of SLC2A1 (p < 0.05), VLDLR (p < 0.01), FABP3 (p < 0.01), and elevated SLC2A1 (p < 0.05) and FASN (p < 0.01) gene expression in the adipose tissue of goats fed the OC20 diet. Overall, OC can be used in goats' diets as a forage replacement, at least in the inclusion rate of 20% DM, since this could increase the milk protein and fat percentage and enrich its content with beneficial for human health lipids without adversely affecting milk production traits.
Keywords: milk fatty acids; ensiled olive cake; gene expression